Pacing and performance in competitive middle-distance speed skating - Mühlbauer, T.; Schindler, C.; Panzer, S. (Research Quarterly for Exercise and Sport, 2010)
Data from speed skating during World Cup 1,500-m middle-distance races were analyzed to (a) determine the time/velocity distribution during the race and (b) assess the impact of time spent in several race sectors on performance outcome. Absolute and relative sector times for the first 300 m (S1) and the following three 400-m laps (S2-S4) and their associations with total race time were analyzed for 53 female and 61 male skaters. Simple regression analyses revealed that both a short relative sector time later in the race (women in S3: p < .001; men in S3: p = .001) and a high relative sector time early in the race (women in S1: p < .001; men in S1: p = .08) were associated with a short total race time in the 1,500-m middle-distance event. These findings suggest that for the best overall time it is important to be as fast as possible later in the race and not quite as fast during the first part of the race. Therefore, speed skating performance may be improved by maintaining a high velocity or by minimizing the decline from a high velocity during later race segments.